JAMINAN FIDUSIA YANG DIJADIKAN JAMINAN KEMBALI DENGAN TIDAK MELAKUKAN PENGHAPUSAN FIDUSIA MENURUT PRESPEKTIF HUKUM DI INDONESIA - Rinal Efries Situmeang; Irene Svinarky; Lisa Simamora (UNES Law Review, 2020)
Fiduciary is shift that did by fiduciary owner to fiduciary receiver, while for up object ability that present on object owner. Number law 42 Years 1999 about Fiduciary Surety or more recognized with UUJF is attributed to make and gives protection of the parties so fiduciary transactions to the fore also expected to qualify law on fiduciary. Fiduciary will erase if object that made by indemnity being paid off by its loan, while is fiduciary was placed to an object really being prohibited for fiduciary giver for vouch in as indemnity is back but a long cry intention of Section 17 UUJF with Section 23 sentences (2) UU JF . In Section 23 sentences (2 ) bear out one of rule it that object that becomes fiduciary indemnity can be shifted if get agreement in writing of fiduciary receiver but variably its thing with what does he meant on Section 25 sentences (1) UUJH. Section 25 sentences (1) UUJH where terminological its formulation that fiduciary indemnity delete because of that fiduciary indemnity is alone was demolish; then indemnity that is used for fiduciary was end its book debt; then fiduciary giver to fiduciary receiver; rights release on fiduciary indemnity by fiduciary receiver; and if goods that becomes fiduciary indemnity disappear therefore fiduciary will erase. Observational type that is used in this research is jurisdictional observational type normative. Fiduciary indemnity terminological UUJF bases Section 17 be borne out that: Information hits indemnity object as object that stills in fiduciary indemnity and still enrolled therefore fiduciary giver is prohibited to do fiduciary and Section 17 not if fiduciary receiver accept therefore get to make that indemnity as back indemnity without ask for fiduciary indemnity deletions as royal. To the effect to list that fiduciary back as surety of giving afters fiduciary fiduciary pays off that goods is subject to be not remove prefentif's rights divides fiduciary receiver.